Pengaruh Lingkungan Kerja, Kepuasan Kerja dan Kompensasi Terhadap Retensi Karyawan Generasi Z di Kota Surakarta - Diyan Agus Mayangsari; Putri Oktovita Sari (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study is a survey study on Generation Z employees in Surakarta City. The purpose of this study is to determine the influence of the work environment, job satisfaction and compensation on the retention of generation Z employees in Surakarta City. The type of data used is quantitative data, the data source used is primary data. Data collection in this study was carried out by distributing questionnaires to the relevant respondents. The population in this study were generation Z employees who worked in Surakarta City and the sampling technique in this study used Purposive Sampling with the criteria of respondents aged over 18 years and working in Surakarta City, and obtained a sample of 130 respondents. Data were collected with questionnaires that had been tested for validity and reliability as well as classical assumption tests. Data analysis techniques used multiple linear regression, t-test, F-test and coefficient of determination (R2). The results of this study indicate that the work environment has a significant effect on the retention of generation Z employees in Surakarta City. Job satisfaction has a significant effect on the retention of generation Z employees in Surakarta City. Compensation does not have a significant effect on the retention of generation Z employees in Surakarta City. The calculated F value is 45.386 with a significance value of 0.000 > 0.05, meaning that the regression model is appropriate for testing the influence of the work environment, job satisfaction, and compensation on employee retention. The coefficient obtained is an adjusted R square value of 0.508, meaning that the contribution of the influence of the work environment, job satisfaction, and compensation to employee retention is 50.8%.